2006
DOI: 10.1144/gsl.mem.2006.032.01.26
|View full text |Cite
|
Sign up to set email alerts
|

Crustal structure of the Middle Urals based on seismic reflection data

Abstract: EUROPROBE-related seismic reflection surveys in the Middle Urals, Russia (latitude 56-62 ~ since 1993 have led to an increased understanding of the crustal structure and tectonic evolution of this region. A 400 km long profile now extends from the foreland basin in the west well into the West Siberian Basin in the east. Bivergent structures characterize the upper crust of the Uralide orogen, whereas the middle and lower crust generally contain gently west-dipping reflections. A crustal root is imaged down to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…In the case of the Urals, the Palaeozoic mountain belt marking the boundary between the East European Craton to the west and the Asian collage of terranes to the east, a 10–15‐km‐thick crustal root has also been identified from controlled‐source seismic studies (Carbonell et al 1996; Knapp et al 1996; Stadtlander et al 1999; Kashubin et al 2009). In the middle Urals there is evidence from seismic data that the western East European Craton has been underthrust by the eastern West Siberian plate (Kashubin et al 2006, 2009), whereas in the southern Urals the picture is less clear. Many other Palaeozoic orogens, for example the Variscides, Caledonides and Appalachians have no crustal root anymore, due to post‐orogenic extension and re‐equilibration of the lithosphere (Berzin et al 1996).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…In the case of the Urals, the Palaeozoic mountain belt marking the boundary between the East European Craton to the west and the Asian collage of terranes to the east, a 10–15‐km‐thick crustal root has also been identified from controlled‐source seismic studies (Carbonell et al 1996; Knapp et al 1996; Stadtlander et al 1999; Kashubin et al 2009). In the middle Urals there is evidence from seismic data that the western East European Craton has been underthrust by the eastern West Siberian plate (Kashubin et al 2006, 2009), whereas in the southern Urals the picture is less clear. Many other Palaeozoic orogens, for example the Variscides, Caledonides and Appalachians have no crustal root anymore, due to post‐orogenic extension and re‐equilibration of the lithosphere (Berzin et al 1996).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…A reflective lower crust is an uncommon feature in the stable cratonic areas and is typically related to crustal extension [ Meissner et al ., ]. However, a similar reflection fabric was detected at the western margin of the EEC in the Baltic Sea [ BABEL Working Group , ; Meissner and Krawczyk , ] and at the eastern margin of the EEC close to Urals [ Kashubin et al ., ]. Both cases are the result of crustal compression.…”
Section: Evolution From a Passive Margin Stage To Polygenetic Crustalmentioning
confidence: 99%
“…These are the URSEIS profile in the southern Urals and the Mikhailovsky and ESRU profiles in the middle Urals ( Figure 1). Crustal scale images derived from these profiles have been presented elsewhere [Echtler et al, 1996;Knapp et al, 1996;Steer et al, 1998;Tryggvason et al, 2001;Juhlin et al, 1998;Friberg et al, 2002;Brown et al, 2002;Kashubin et al, 2005], and their acquisition parameters and processing flow can be found in these publications. Here we present only that part of each profile that corresponds to the foreland thrust and fold belt and the transition into the undeformed foreland basin.…”
Section: Structure Of the Foreland Thrust And Fold Beltmentioning
confidence: 99%
“…Reflection seismic data (the Urals Seismic Experiment and Integrated Studies (URSEIS), Mikhailovsky, and Europrobe's Seismic Reflection Profiling in the Urals (ESRU) profiles) form the main data set, together with surface geology from our own mapping and published 1:200,000-scale geological maps (Geology of the USSR: 1:200,000 Urals Map Series). Two of the reflection seismic profiles, Mikhailovsky (MIK in Figure 1) and a westward extension of ESRU are new, having been recently acquired in the middle Urals [Kashubin et al, 2005]. In the southern Urals, balanced and restored cross sections have been previously constructed across the foreland thrust and fold belt Perez-Estaun et al, 1997].…”
Section: Introductionmentioning
confidence: 98%